2001
DOI: 10.1364/josaa.18.002398
|View full text |Cite
|
Sign up to set email alerts
|

Perception of forbidden colors in retinally stabilized equiluminant images: an indication of softwired cortical color opponency?

Abstract: In color theory and perceptual practice, two color naming combinations are forbidden-reddish greens and bluish yellows-however, when multicolored images are stabilized on the retina, their borders fade and filling-in mechanisms can create forbidden colors. The sole report of such events found that only some observers saw forbidden colors, while others saw illusory multicolored patterns. We found that when colors were equiluminant, subjects saw reddish greens, bluish yellows, or a multistable spatial color exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 26 publications
1
58
0
Order By: Relevance
“…Surprisingly, something like that conscious experience seems actually to occur; in a striking study, Billock et al [81] found that when multi-coloured, equiluminant images are stabilized on the retina, some subjects report seeing reddish greens or bluish yellows, presumably owing to filling-in mechanisms. But higher-order theories are in any case not committed to such predictions.…”
Section: (F ) Misrepresentation and What It Is Likementioning
confidence: 99%
“…Surprisingly, something like that conscious experience seems actually to occur; in a striking study, Billock et al [81] found that when multi-coloured, equiluminant images are stabilized on the retina, some subjects report seeing reddish greens or bluish yellows, presumably owing to filling-in mechanisms. But higher-order theories are in any case not committed to such predictions.…”
Section: (F ) Misrepresentation and What It Is Likementioning
confidence: 99%
“…Ordinary human beings are said to have colour perceptions that require a description which contradicts our ordinary colour concepts (cf. Billock et al 2001Billock et al , p. 2398. It is claimed that it is possible to perceive reddish green and bluish yellow under the following special conditions.…”
Section: Wittgenstein On Conceptual Arbitrarinessmentioning
confidence: 99%
“…Billock, Gleason, and Tsou write: "Our subjects (...) were tongue-tied in their descriptions of these colors, using terms like 'green with a red sheen,' or 'red with green highlights'." (Billock et al 2001(Billock et al , p. 2398) Using these terms for what; answering which question? Apparently, they did not use the term "reddish green".…”
Section: Wittgenstein On Conceptual Arbitrarinessmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulus was adjacent red and green stripes (or blue and yellow stripes); when the stimulus was held in the same position relative to the participants' eyes, some of the subjects experienced reddish-green or bluishyellow. The study was successfully repeated by Vincent Billock et al (2001), who also adjusted for variation in luminance. Despite the fact that some subjects can experience reddish-green and bluish-yellow, these shades of color have no instantiated physical color correlates.…”
Section: Color Physicalismmentioning
confidence: 99%